Immunohistochemistry on pattern of ocular & adnexal tumours in a tertiary eye care centre of Northeast India - Das, Dipankar (Indian J Med Res, 2018)
BACKGROUND & OBJECTIVES: Ocular and adnexal tumours are important causes of morbidity in India and globally. Immunohistochemistry (IHC) is a vital molecular pathology tool, which helps to diagnose a tumour with more accuracy. The present study was undertaken to document the profile of ocular and adnexal tumour with IHC at a tertiary eye care center in Northeast India. METHODS: This was a prospective and laboratory-based study. Histopathological and IHC study of the ocular and adnexal tumour was carried out from 2012 to 2014. Selection of pathological cases was made on the result of the histological diagnosis. All samples were subjected to IHC using kits for different antibodies as per indications. RESULTS: In total, 645 tumours were included in our study, with 449 benign conditions and 196 were malignant tumours. Total IHCs were done in 87 tumours and 238 of antibodies were used. Non-Hodgkin's lymphomas (B-cell, low-to-intermediate type and mucosal-associated lymphoid tumours) were the most common tumor. INTERPRETATION & CONCLUSIONS: Clinical utility of the IHCs in different ophthalmic tumours can enable pathologists to make an accurate diagnosis and thus help in the overall management of the patient care. IHC may be carried out using various methods and some of the methods practiced are time consuming and tedious. In this study, kit methods were used which were found to be simpler and less time-consuming.